PENYULUHAN TENTANG DEMAM TIFOID DI SMA NEGERI 01 KOTABUMI LAMPUNG UTARA - Bahjatun Nadrati; Zuhratul Hajri; Sri Suharti (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2019)
ABSTRACT: THE ANKLE BRACHIAL INDEX AMONG PATIENTS WITH TYPE 2 DIABETES IN WEST LOMBOK-INDONESIABackground: Diabetes spreads throughout the provinces in Indonesia. One of them in the Province of West Nusa Tenggara (NTB), the prevalence of DM diagnosed is 0.9% of the total population. Peripheral vascularization disturbance that occur in people with DM need to be known from the beginning. One effort to determine the existence of disorders peripheral vascularization is by examining the ankle brachial index (ABI).Purpose: To determine the description of the value of the Ankle Brachial Index (ABI) of people with DM in the DM group.Methods: Descriptive study with a population of 25 patients with a total sampling technique. The instrument used is the observation sheet.Results: Most women with DM were as many as 17 patients (68%), most people with DM at the age of 46 - 55 years (68%), the value of ABI with DM with normal interpretations of the right ABI 22 patients (88%) and left ABI 23 patients (92%), right borderline perfusion ABI occurred at the age of 56 - 65 years as many as 2 patients (66.7%), borderline perfusion left ABI occurred at the age of 56-65 years as many as 2 patients (100%), borderline perfusion Right ABI occurred in 2 female respondents (66.7%), borderline perfusion left ABI occurred in female respondents as many as 2 patients (100%).Conclusion: In an effort to improve the health status of the community, especially DM persons, it is expected that the Gunung Sari Health Center in West Lombok Regency can control people with DM in participating in the Puskesmas program, especially DM. Keywords: Ankle Brachial Index (ABI), Type 2 Diabetes Pendahuluan: Penyakit diabetes menyebar diseluruh provinsi di Indonesia. Salah satunya di Provinsi Nusa Tenggara Barat (NTB), prevalensi DM yang sudah terdiagnosis adalah 0,9% dari jumlah total penduduk. Gangguan vaskularisasi perifer yang terjadi pada penyandang DM perlu diketahui dari awal. Salah satu upaya untuk mengetahui adanya gangguan vaskularisasi perifer adalah dengan melakukan pemeriksaan ankle brachial index (ABI).Tujuan : Mengetahui gambaran nilai Ankle Brachial Index (ABI) penyandang DM pada kelompok penyandang DM.Metode : Penelitian deskriptif dengan populasi 25 pasien dengan teknik pengambilan sampel total sampel. Instrumen yang digunakan adalah lembar observasi.Hasil penelitian: Penyandang DM terbanyak dialami oleh perempuan yaitu sebanyak 17 pasien (68%), penyandang DM terbanyak pada usia 46 – 55 tahun (68%), nilai ABI penyandang DM dengan interpretasi normal ABI kanan 22 pasien (88%) dan ABI kiri 23 pasien (92%), borderline perfusion ABI kanan terjadi pada usia 56 – 65 tahun yaitu sebanyak 2 pasien (66,7%), borderline perfusion ABI kiri terjadi pada usia 56-65 tahun sebanyak 2 pasien (100%), borderline perfusion ABI kanan terjadi pada responden perempuan sebanyak 2 pasien (66,7%), borderline perfusion ABI kiri terjadi pada responden perempuan sebanyak 2 pasien (100%).Simpulan: Dalam upaya untuk meningkatkan derajat kesehatan masyarakat khususnya penyandang DM diharapkan Puskesmas Gunung sari Kabupaten Lombok Barat, dapat mengontrol penyandang DM dalam mengikuti program puskesmas khususnya DM.